Caspase-1 Abrogates the Salutary Effects of Hypertrophic Preconditioning in Pressure Overload Hearts via IL-1β and IL-18 - Dai, Fangjie; Li, Xuan; Li, Xia; Ding, Zhiwen; Xu, Ran; Yin, Peipei; Wang, Shijun; Ge, Junbo; Wu, Jian; Zou, Yunzeng (Frontiers in Molecular Biosciences, 2021)
Cardiac hypertrophic preconditioning (HP) signifies cardioprotection induced by transient pressure overload to resist hypertrophic effects of subsequent sustained pressure overload. Although it is recently found that inflammation triggers the development of nonischemic cardiomyopathy, whether inflammation plays a role in the antecedent protective effects of HP remains unknown. Caspase-1 is a critical proinflammatory caspase which also induces pyroptosis, we thus investigated the role of caspase-1 using a unique model of HP in mice subjected longitudinally to 3 days of transverse aortic constriction (TAC 3d), 4 days of de-constriction (De-TAC 4d), and 4 weeks of Re-TAC (Re-TAC 4W). Echocardiography, hemodynamics, histology, PCR and western blot confirmed preserved cardiac function, alleviated myocardial hypertrophy and fibrosis, and less activated hypertrophic signaling effectors in Re-TAC 4W mice, compared with TAC 4W mice. Mechanistically, caspase-1 and its downstream targets IL-1β and IL-18, but not GSDMD, were less activated in Re-TAC 4W mice. Furthermore, In HP mice with AAV-9 mediated cardiac specific caspase-1 overexpression, the salutary effects of HP were remarkably abrogated, evidenced by exacerbated cardiac remodeling, dysfunction, and activation of IL-1β and IL-18. Collectively, this study revealed a previously unrecognized involvement of caspase-1 in cardiac HP by regulation of IL-1β and IL-18, and shed light on caspase-1 as an antecedent indicator and target for cardiac hypertrophy.